The last book on the left : stories of murder and mayhem from history's most notorious serial killers - Kissel, Ben; Parks, Marcus; Zebrowski, Henry (Houghton Mifflin Harcourt, 2020)
"An equal parts haunting and hilarious deep-dive review of history's most notorious and cold-blooded serial killers, from the creators of the award-winning Last Podcast on the Left"--